+0  
 
0
198
4
avatar+3171 

The equation \(y = \frac{x + A}{Bx + C}\), where \(A,B,\) and \(C\)  are integers, is shown below. What is \(A + B + C\)?

https://latex.artofproblemsolving.com/a/c/0/ac0cfb3f53a94da8604511d000667db714ff61b9.png

tertre  Feb 5, 2018
 #1
avatar+7324 
+3

Here's one method...

 

There appears to be an asymptote at  x = 2 , so we know that when  x = 2 ,  Bx + C  =  0

 

B(2) + C  =  0

 

If we solve  \(y=\frac{x+A}{Bx+c}\)  for  x , we get  \(x=\frac{A-Cy}{By-1}\)

 

There appears to be an asymptote at  y = -1 , so we know that when  y = -1 ,  By - 1  =  0

 

B(-1) - 1  =  0

B  =  -1              Use this value for  B  to find  C .

 

(-1)(2) + C  =  0

C  =  2

 

And the graph passes through the point  (0, -2) , so...

 

\(-2 = \frac{0 + A}{-1(0) + 2} \\ -2=\frac{A}{2}\)

-4  =  A

 

Here's a graph of  \(y=\frac{x-4}{-1x+2}\)https://www.desmos.com/calculator/ibji5giqge

 

A + B + C   =   -4 + -1 + 2   =   -3

hectictar  Feb 5, 2018
 #2
avatar+89775 
+1

Very nice, hectictar.....!!!

 

 

cool cool cool

CPhill  Feb 5, 2018
 #3
avatar+3171 
+2

Amazing, hectictar!

tertre  Feb 5, 2018
 #4
avatar+89775 
+3

Here's one more approach....

 

Note that the points    (0, - 2)  (3,1)  and (4,0)  are on the graph

 

So....we must have that

 

0 =  4 + A    ⇒  A  =  -4

 

And

 

-2  =  [0 + (-4)]  / [B (0) + C ]

 

-2  +  -4 / C

 

-2C  = - 4    ⇒  C  =  2

 

And

 

1  =  [ 3 + (-4) ] / [ B(3) + 2 ]

 

1 =  - 1 / [ 3B + 2]

 

3B + 2  =  - 1

 

3B =  -3  ⇒   B =  -1

 

So....A + B + C     =     -4 - 1 + 2    =    -3

 

 

cool cool cool

CPhill  Feb 6, 2018

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.